S-Nitrosylation of α1-Antitrypsin Triggers Macrophages Toward Inflammatory Phenotype and Enhances Intra-Cellular Bacteria Elimination - Kaner, Ziv; Engelman, Rotem; Schuster, Ronen; Rider, Peleg; Greenberg, David; Av-Gay, Yossef; Benhar, Moran; Lewis, Eli C. (Frontiers in Immunology, 2019)
Background. Human α1-antitrypsin (hAAT) is a circulating anti-inflammatory serine-protease inhibitor that rises during acute phase responses. In vivo, hAAT reduces bacterial load, without directly inhibiting bacterial growth. In conditions of excess nitric-oxide (NO), hAAT undergoes S-nitrosylation (S-NO-hAAT) and gains antibacterial capacity. The impact of S-NO-hAAT on immune cells has yet to be explored. Aim. Study the effects of S-NO-hAAT on immune cells during bacterial infection. Methods. Clinical-grade hAAT was S-nitrosylated and then compared to unmodified hAAT, functionally and structurally. Intracellular bacterial clearance by THP-1 macrophages was assessed using live Salmonella typhi. Murine peritoneal macrophages were examined, and signaling pathways were evaluated. S-NO-hAAT was also investigated after blocking free mambranal cysteine residues on cells. Results. S-NO-hAAT (27.5 uM) enhances intracellular bacteria elimination by immunocytes (up to 1-log reduction). S-NO-hAAT causes resting macrophages to exhibit a pro-inflammatory and antibacterial phenotype, including release of inflammatory cytokines and induction of iNOS and TLR2. These pro-inflammatory effects are dependent upon cell surface thiols and activation of MAPK pathways. Conclusions. hAAT duality appears to be context-specific, involving S-nitrosylation in a nitric oxide rich environment. Our results suggest that S-nitrosylation facilitates the antibacterial activity of hAAT by promoting its ability to activate innate immune cells. This pro-inflammatory effect may involve transferring of nitric oxide from S-NO-hAAT to a free cysteine residue on cellular targets.